MANAJEMEN RISIKO BEKERJA DI KETINGGIAN PROYEK PLTGU JAWA SATU POWER CILAMAYA DENGAN METODE HIRADC (HAZARD IDENTIFICATION RISK ASSESSMENT AND DETERMINING CONTROL) - Fauzan Fawwazillah (FT-USNI, 2021)
PT. Berca Buana Sakti Indonesia is a multidisciplinary contractor with experience and resources who provide the best service in the field of engineering and construction diversity. The purpose of this study is to analyze potential hazards, assess risks, control risks in the Java One Power Cilamaya Hydropower Project. The development process carried out by PT. Berca Buana Sakti has the possibility of high hazards and risks in the project area that causes work accidents. Therefore, the potential danger should be analyzed with one of the risk analysis methods, namely HIRADC (Hazard Identification Risk Assessment and Determining Control). The HIRADC method is used to analyze existing hazards, determine risk assessments and group each hazard based on the level of risk. From the analysis of assessment of K3 risk known risk rank, there are 44 types of low risk risk, 21 types of medium risk risk and 0 types of high risk. HIRADC method can reduce the potential for work accidents by conducting management of a series of activities carried out. PT. Berca Buana Sakti implements elimination control, engineering modification, and personal protective equipment (PPE) to reduce accidents and risk management and also has excellent results in knowledge and behavior related to occupational safety and health and good on knowledge of HIRADC.